2005
DOI: 10.1093/gerona/60.11.1386
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Accelerated Cell Aging in Werner Syndrome Using a p38 Mitogen-Activated Protein Kinase Inhibitor

Abstract: We investigated the role of p38 mitogen-activated protein kinase (MAPK) signalling in the accelerated aging of Werner Syndrome (WS) fibroblasts by use of SB203580, a cytokine-suppressive anti-inflammatory drug that targets p38 activity. SB203580 treatment reverts the aged morphology of young WS fibroblasts to that seen in young normal fibroblasts. In addition, SB203580 increases the life span and growth rate of WS fibroblasts to within the normal range. In young WS cells, p38 is activated coincident with an up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
148
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(159 citation statements)
references
References 36 publications
11
148
0
Order By: Relevance
“…We first examined p38 activation, as this marker was also shown to be involved in senescence of WS fibroblasts (51). A proportional increase in p38 expression and phosphorylation levels was noted in the liver of Wrn Δhel/Δhel animals compared to WT mice, but ascorbate had no effect on these changes (Fig.…”
Section: Vitamin C Normalizes Several Wrn δHel/δhel Mouse Liver Stresmentioning
confidence: 99%
“…We first examined p38 activation, as this marker was also shown to be involved in senescence of WS fibroblasts (51). A proportional increase in p38 expression and phosphorylation levels was noted in the liver of Wrn Δhel/Δhel animals compared to WT mice, but ascorbate had no effect on these changes (Fig.…”
Section: Vitamin C Normalizes Several Wrn δHel/δhel Mouse Liver Stresmentioning
confidence: 99%
“…The AT and WS fibroblasts early in their replicative lifespan are reported to show an altered, enlarged, cellular morphology due to the presence of extensive networks of F-actin stress-fibres (Davis et al 2005;McKinnon and Burgoyne 1985), and resemble normal fibroblasts that have undergone stress-induced premature senescence (SIPS) as a result of oncogenic ras expression or arsenite treatment (Deng et al 2004;Guay et al 1997;Huot et al 1997;Wang et al 2002). These features of SIPS can result from activation of the stress-associated p38a MAP kinase as the use of the p38 selective inhibitor SB203580 prevents ras-induced senescence in human BJ fibroblasts (Deng et al 2004;Wang et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that WS fibroblasts have a normal lifespan and cellular morphology when treated with the p38 inhibitor SB203580; in effect SB203580 prevents the accelerated ageing that is a hallmark of WS cells (Davis et al 2005). Thus, the accelerated ageing is thought to be due to SIPS, and the p38 signalling pathway is activated in cultures of young WS cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the p38MAPK gene product is activated in fibroblasts from Werner syndrome patients (Davis et al, 2005). However, it is unclear what role p38MAPK may play in adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The implication is that Wrn is involved in modulating p38MAPK activity. This concept is of interest since a recent study by Davis et al, (2005) showed that treatment of human WS cells with a p38MAPK inhibitor could reverse this senescent phenotype.…”
Section: Discussionmentioning
confidence: 99%